FAKTOR FAKTOR YANG MEMPENGARUHI KEPATUHAN DOKTER DALAM PELAKSANAAN ENAM LANGKAH LIMA MOMEN CUCI TANGAN DI RUANG RAWAT JALAN RSUD WANGAYA KOTA DENPASAR - Ni Nengah Juniasih; I Putu Dedy Kastama Hardy; Ni Ketut Martini (LPPM Universitas Dhyana Pura, 2019)
ABSTRACTNosocomial infection is an infection due to the transmission of pathogenic organisms to previously uninfected patients from the hospital environment. Infection that occurs can be caused by several ways, including compliance with hand washing. Infection prevention and control must be done by doctors, nurses and all people involved in patient care, one of which is by washing hands properly. Usingcross sectional research design with total sampling sampling techniquefrom January to May 2019. The respondents were 66 respondents weredoctors assigned to the Outpatient Installation of Wangaya Hospital, Denpasar City. Showed that there was no significant relationship between doctor's knowledge of adherence p = 0, 538 (p = <0.05). There is no significant relationship between attitudes toward compliance p = 0, 839 (p = <0.05) and only the facility variable have significant relationshiptoward compliance p = 0, 026 (p = <0.05). Conclusions and suggestions based on this matter are suggested to the PPI of Wangaya Hospitelto improve compliance with handwashing by making education programs and ongoing monitoring, collaborative proscedures and common perceptions of hand hygiene, the existence of reward and the availability of hand hygiene facilities and infrastructure and physician compliance in implementation of handwashing.Keywords: Compliance, knowledge, attitude, facilities, hand washing